ANALISIS KEMAMPUAN REPRESENTASI VISUAL DAN REPRESENTASI VERBAL MAHASISWA PADA MATERI MORFOLOGI TUMBUHAN SERTA HUBUNGANNYA DENGAN KEMAMPUAN VISUAL DAN KEMAMPUAN VERBAL UMUM: ANALYSIS OF VISUAL REPRESENTATION AND VERBAL REPRESENTATION OF STUDENTS ON PLANT MORPHOLOGY MATERIALS AND ITS RELATIONSHIP TO VISUAL AND VERBAL ABILITIES - Stevia Ladisa; Adi Rahmat; Bambang Supriatno (Jurnal Psikologi Jambi, 2020)
Introduction The main study of plant morphology is about the appearance of plants as a whole and the scientific terms (terminology) used in recognizing plants. In the plant morphology undergraduate students are directed to understand the basic concepts and knowledge about plants and their terminology through learning activities and practicum in laboratory, so that undergraduate students can get complete information about the plants being studied. The information will be organized in working memory to produce a knowledge that can be represented both visually and verbally.Method The aims of this study was to analyze the ability of visual representation and verbal representation of undergraduate students on leaf concepts, analyze visual abilities and verbal abilities, analyze the corellation between visual representation abilities and verbal representation of leaf concepts with visual abilities and verbal abilities of undergraduate students. This research was a descriptive study at the Indonesian University of Education in the plant morphology course of leaf concepts with 30 participants.Results of this study showed that the visual representations of undergraduate students on leaf concepts has moderately correlated with visual abilities of undergraduate students. The verbal representations of undergraduate students on leaf concepts has low correlated with undergraduate students' verbal abilities.Conclusions And Recommendations This result also showed that the good ability of visual representation cannot always be described with good visual abilities, as well as good verbal representation cannot always be described with good verbal abilities.Keywords: visual representation, verbal representation, visual ability, verbal ability. ABSTRAK Pendahuluan Kajian utama morfologi tumbuhan adalah tentang penampilan tumbuhan secara utuh serta istilah-istilah ilmiah (terminologi) yang digunakan dalam mengenali tumbuhan. Pada mata kuliah morfologi tumbuhan mahasiswa diarahkan untuk memahami konsep dan pengetahuan dasar tentang tumbuhan dan terminologinya melalui kegiatan pembelajaran dan praktikum, sehingga mahasiswa dapat memperoleh informasi yang utuh tentang tumbuhan yang dipelajari. Informasi tersebut akan diorganisasikan dalam memori (working memory) sehingga menghasilkan sebuah pengetahuan yang dapat direpresentasikan baik secara visual maupun secara verbal. Metode Tujuan penelitian ini adalah untuk menganalisis kemampuan representasi visual dan representasi verbal mahasiswa pada materi daun, menganalisis kemampuan visual dan kemampuan verbal umum serta menganalisis hubungan antara kemampuan representasi visual dan representasi verbal materi daun dengan kemampuan visual dan kemampuan verbal umum mahasiswa. Penelitian ini merupakan penelitian deskriptif yang dilaksanakan di Universitas Pendidikan Indonesia pada mata kuliah morfologi tumbuhan materi daun dengan 30 orang mahasiswa. Hasil penelitian ini menggambarkan bahwa kemampuan representasi visual mahasiswa tentang materi daun berkorelasi sedang dengan kemampuan visual umum mahasiswa. Sedangkan kemampuan representasi verbal mahasiswa tentang materi daun berkorelasi rendah dengan kemampuan verbal umum mahasiswa. Kesimpulan dan rekomendasi Hasil ini juga menunjukan bahwa kemampuan representasi visual yang baik tidak selalu dapat digambarkan dengan kemampuan visual umum yang baik, begitu juga dengan kemampuan representasi verbal yang baik tidak selalu dapat digambarkan dengan kemampuan kemampuan verbal umum yang baik. Kata Kunci: representasi visual, representasi verbal, kemampuan visual, kemampuan verbal.